Discriminative spatial localisation in confocal reflectance and carbon dots-based fluorescence imaging using mixed-mode endoscopic scanner - Yang Sing Leong; Mohd Hadri Hafiz Mokhtar; Nur Afifah Ahmad Nazri; Mohd Hafiz Abu Bakar; Mohd Saiful Dzulkefly Zan; Norhana Arsad; Peer Mohamed Abdul; Ahmad Ashrif A. Bakar (International Journal of Optomechatronics)
Carbon dots (CDs)-based fluorescence imaging with confocal reflectance effectively localises labelled structures with clear sample visualization. Yet, integrating these modalities into single-fibre cantilever-based endoscopic scanners poses challenges. Thus, we present an endoscopic scanner with a mixed-mode fibre cantilever for dual modalities imaging. The cantilever features two-attached fibre construction for multiple illumination and detection channels without additional optical components. The measured lateral and axial resolutions are 5.81 and 6.52 µm, respectively with field-of-view of 408 × 488 µm. The fluorescence detection capability was first verified using fluorescent microspheres and CD-embedded polymer film, followed by confocal reflectance and CDs-based fluorescence imaging on labelled fibrous network and plant samples. The results demonstrate the complementary strengths of confocal reflectance, which extracts surface profiles, and CDs-based fluorescence, which captures fluorescence signals, leading to precise localization of fluorescence signals within the sample. Switching modality schemes at the scanner’s back-end enables implementation of different modalities.